1989
DOI: 10.3109/08916938908997095
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive Cytotoxic T Lymphocytes in Pemphigus and Pemphigoid

Abstract: In order to know whether effector cells are capable of recognizing the epidermal targets in pemphigus vulgaris (PV) and bullous pemphigoid (BP), non-adherent cells (NAC) of peripheral blood from 27 primary PV, 19 BP patients and 12 healthy volunteers were used in cytotoxic tests. Autologous, allogenic and murine epidermal keratinocytes as well as autologous and allogenic fibroblasts were employed as targets. Total esterase activity of serine proteinases was measured in supernatants of samples and the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
4

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
11
0
4
Order By: Relevance
“…Both humoral (38) and cellular (39) effectors of autoimmune aggression against KC are involved in the pathogenesis of this disease, and it has been demonstrated that local activation of trypsin-like serine proteases, such as plasminogen activator (40), complement (41), eicosanoids (42), and proinflammatory cytokines (29,43), all can contribute to acantholysis. The precise mechanism leading to acantholysis in PV, however, is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Both humoral (38) and cellular (39) effectors of autoimmune aggression against KC are involved in the pathogenesis of this disease, and it has been demonstrated that local activation of trypsin-like serine proteases, such as plasminogen activator (40), complement (41), eicosanoids (42), and proinflammatory cytokines (29,43), all can contribute to acantholysis. The precise mechanism leading to acantholysis in PV, however, is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Using an organ culture model of PV, it has been demonstrated that PVIgG works together with FasL and tumor necrosis factor ␣ to induce apoptolysis (22). These and some other mediators of inflammation were found to be elevated in skin and/or serum of PV patients (16,19,(23)(24)(25).…”
Section: Pemphigus Vulgaris (Pv)mentioning
confidence: 99%
“…Subsequent studies demonstrated that PVIgG binding to KCs causes secretion of soluble FasL, increased production and cellular amounts of FasR and FasL (soluble and membranal), co-aggregation of FasL and FasR with caspase 8 in a membranal deathinducing signaling complex, and down-regulation of the apoptosis inhibitor FLIP-l (5,10,11,14,27,28). The keratinocyte FasR can be also triggered by FasL expressed by the cytotoxic T cells (29) found in the skin of PV patients (30). Dr. Pincelli and co-workers (31) have recently reported that FasL neutralizing antibody can prevent PVIgG-induced apoptolysis both in vitro and in vivo .…”
Section: Pemphigus Vulgaris (Pv)mentioning
confidence: 99%
“…These diseases include: (1) cutaneous GVHD, in which engrafted CTLs kill recipient epidermal keratinocytes [94]; (2) toxic epidermal necrolysis, in which Fas-ligand-expressing immune cells kill Faspositive keratinocytes [95]; (3) lichenoid tissue reactions, in which autologous CTLs kill keratinocytes by a soluble factor-based mechanism [96]; and (4) pemphigus vulgaris and bullous pemphigoid, in which autoreactive CTLs are present in lesional skin and the circulation of affected patients [97]. Cell-mediated cytotoxicity in pemphigus vulgaris is known to involve both autoreactive CD8þ CTLs [97] and the patient's IgGs, which recruit allogeneic peripheral blood mononuclear cells to induce antibody-dependent cellular cytotoxicity in epithelial targets [98,99]. It has been suggested that in PAMS the IgGs putatively responsible for the development of the disease may, in a similar mechanism, reflect or even induce the cell-mediated immune response that accounts for the wide range of pathologic effects seen in the disease [5].…”
Section: Humoral and Cytotoxic Immunity In Pamsmentioning
confidence: 99%